Waqf institutions in Malaysia: appreciation of Wasaṭiyyah approach in internal control as a part of good governance - Mohd. Zain, Nor Razinah; Hassan, Rusni; Mustaffha, Nazifah (International Islamic University Malaysia, 2018)
Good governance is important for the sustainability of Waqf institutions in Malaysia. As a part of good governance, the evaluation of internal control and its components are essential to be considered. While reaching the Maqāṣid al-Sharī‘ah (the objectives of the Lawgiver), the appreciation of Wasaṭiyyah approach can be utilised in the evaluation of internal control in the Waqf institutions. Based on qualitative research method, this research explores the internal control and its components in Waqf institutions. The conceptual study on Wasaṭiyyah approach is provided in brief, and the appreciation of Wasaṭiyyah approach in relation to internal control and its components are provided. It is found that Wasaṭiyyah approach can be used in the evaluation of internal control of Waqf institutions in improving their good governance. ********************************************************* Tadbir urus yang baik adalah penting untuk kelestarian institusi Waqfdi Malaysia. Sebagai sebahagian daripada tadbir urus yang baik, penilaian kawalan dalaman dan komponennya penting untuk dipertimbangkan. Bagi mencapai Maqāsid al-Sharī’ah, penghargaan terhadap pendekatan Wasaṭiyyahseharusnya dihayati dalam penilaian kawalan dalaman dalam institusi Waqf. Berdasarkan kaedah penyelidikan kualitatif, penyelidikan ini menghuraikan kawalan dalaman dan komponennya dalam institusi Waqf. Kajian konseptual mengenai pendekatan Wasaṭiyyah ini disediakan secara ringkas, dan penghargaan terhadap pendekatan Wasaṭiyyah berkaitan dengan pengendalian secara kawalan dalaman dan komponennya adalah disediakan. Adalah didapati bahawa pendekatan Wasaṭiyyah dalam penilaian kawalan dalaman institusi Waqf dapat meningkatkan tadbir urus institusi Waqf secara baik dan berkesan.